HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KEPERCAYAAN DIRI ANAK DALAM BELAJAR DI SEKOLAH KELAS V DAN VI SDN PASIR AWI TAHUN 2020 - Elliska Tias Irmani; H.A.Y.G. Wibisono; Febi Ratnasari (Nusantara Hasana Journal, 2021)
Self-confidence or self-confidence is an attitude that is owned by individuals who can develop well, but can also experience a decline which can make it difficult for the individual to even not want to do something. Therefore, the support and role of parents is very important to foster and increase children's confidence in learning and the importance of parenting for children. Objective: To determine the relationship between parenting styles and children's self-confidence in learning at school. Methods: This study uses a descriptive correlation design, the sampling technique uses a proposionate startified random sampling. The sample in this study were 109 respondents. Using univariate and bivariate analysis and the Kolmogorov-Smirnov normality test. Results: Based on the chi suare test (P value 0.004 <0.05). There is a significant relationship between the variables of parenting style and self-confidence. Conclusions and Suggestions: Most of the respondents belong to the dominance of democratic parenting with optimistic self-confidence. Providing information is intended to increase knowledge in child care or choose parenting, so that it can support and increase children's self-confidence in learning.